Does Accidental Hypothermia Increase Morbidity and Mortality in Mature Neonates? - Petersen, Lisa; Kainer, Franz; Schroth, Michael Andreas (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Accidental hypothermia in mature neonates requiring hospitalization is a clinical complication that has not been studied in detail. In the present study, the effect of accidental hypothermia on common morbidity in neonates in the postnatal period was investigated. We did temperature measurements in 616 mature neonates after birth, after transfer to the maternity ward and at check-up at age of 48–72 hours of life. Additionally, nurses checked temperature until discharge at every diaper change in 302 of all included neonates who were small for gestational age (SGA) or whose mothers had green fluid or premature rupture of membranes (PROM). We investigated if there was a correlation between infection, hyperbilirubinemia, hypoglycemia, SGA, gestational diabetes, PROM, green amniotic fluid, positive GBS status of the mother, and accidental hypothermia in the first 48–72 hours of life. Mature neonates showed transient accidental hypothermia in the first 24 hours of life. No significant correlation between infection (p=0.571), hyperbilirubinemia (p=0.837), hypoglycemia (p=0.072), and accidental hypothermia could be seen. There was a significant correlation between SGA (p=0.020), PROM (p=0.008), and accidental hypothermia, while hyperthermia was associated with infection (p=0.009) and green amniotic fluid (p=0.004). SGA and PROM represent perinatal risk factors for postnatal transient accidental hypothermia in mature neonates. Increased morbidity or mortality associated with postnatal accidental hypothermia has not been demonstrated.Akzidentelle Hypothermie bei Reifgeborenen, die einer Hospitalisierung bedürfen, ist eine bisher nicht näher analysierte klinische Komplikation. In der vorliegenden Arbeit wurde die Abhängigkeit einer akzidentellen Hypothermie von typischen Erkrankungen der Postnatalperiode untersucht. Wir führten bei 616 Reifgeborenen Temperaturmessungen nach Geburt, nach Verlegung auf die Wochenstation und bei der Vorsorgeuntersuchung U2 durch. Zusätzlich kontrollierten wir bei 302 der 616 Neugeborenen mit Small for gestational age (SGA), grünem Fruchtwasser oder vorzeitigem Blasensprung (PROM) die Temperatur bei jedem Windelwechsel bis zur Entlassung. Wir untersuchten, ob es einen Zusammenhang zwischen Infektion, Hyperbilirubinämie, Hypoglykämie, SGA, Gestationsdiabetes, PROM, grünem Fruchtwasser, positivem GBS-Status der Mutter und akzidenteller Auskühlung innerhalb der ersten 48–72 Lebensstunden gab. Reifgeborene zeigten in den ersten 24 Lebensstunden transiente akzidentelle Hypothermien. Es konnte kein signifikanter Zusammenhang zwischen Infektion (P=0.571), Hyperbilirubinämie (p=0.837), Hypoglykämie (p=0.072) und akzidenteller Hypothermie festgestellt werden. Es bestand ein signifikanter Zusammenhang zwischen SGA (p=0.020), PROM (p=0.008) und akzidenteller Hypothermie, während Hyperthermie war mit Infektion (p=0.009) und grünem Fruchtwasser (p=0.004) assoziiert war. SGA und PROM stellen perinatale Risikofaktoren für postnatale transiente, akzidentelle Hypothermien bei Reifgeborenen dar. Eine erhöhte Morbidiät bzw. Mortalität im Zusammenhang mit postnataler akzidenteller Hypothermie konnte nicht nachgewiesen werden.
Keywords: Accidental hypothermia; Perinatal risk factors; Entities of postnatal period; neonatal thermal monitoring